Attributable mortality to radon exposure in Galicia, Spain. Is it necessary to act in the face of this health problem? - Barros-Dios Juan M; Pérez-Ríos Mónica; Montes-Martínez Agustín; Ruano-Ravina Alberto (BMC, 2010)
Abstract Background Radon is the second risk factor for lung cancer after tobacco consumption and therefore it is necessary to know the burden of disease due to its exposure. The objective of this study is to estimate radon-attributable lung cancer mortality in Galicia, a high emission area located at the Northwest Spain. Methods A prevalence-based attribution method was applied. Prevalence of tobacco use and radon exposure were obtained from a previously published study of the same area. Attributable mortality was calculated for each of six possible risk categories, based on radon exposure and smoking status. Two scenarios were used, with 37 Bq/m3 and 148 Bq/m3 as the respective radon exposure thresholds. As the observed mortality we used lung cancer mortality for 2001 from the Galician mortality registry. Results Mortality exclusively attributable to radon exposure ranged from 3% to 5% for both exposure thresholds, respectively. Attributable mortality to combined exposure to radon and smoking stood at around 22% for exposures above 148 Bq/m3. Applying the United States Environmental Protection Agency (EPA) action level, radon has a role in 25% of all lung cancers. Conclusions Although the estimates have been derived from a study with a relatively limited sample size, these results highlight the importance of radon exposure as a cause of lung cancer and its effect in terms of disease burden. Radon mitigation activities in the study area must therefore be enforced.